Bioâdigestion andÂ postâtreatment ofÂ effluents byÂ bioâfermentation, anÂ opportunity forÂ energy uses andÂ generation ofÂ organic fertilizers fromÂ bovine manure - Luis Antonio Barzallo-Bravo; David Carrera-VillacrÃ©s; Rafael Eduardo Vargas-Verdesoto; Lourdes Karina Ponce-Loaiza; Modesto Correoso; Ãlvaro Petronio Gavilanes-Quishpi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Bio-fermentation has been routed as a viable alternative for the treatment of organic waste, which can provide renewable energy and can return nutrients to the soil with its byproducts. In this context, the objectives of the research were to analyze the benefits that a plastic plug-flow bio-digester can provide for treatment of bovine manure; and through biofermentation to control the E. coli number present in the bio-digester effluents. Methods The concentration of macronutrients and amount of the E. coli in the effluent was determined by the methods of analysis purposed by APHA standard methods and AOAC standard methods, respectively. In addition, the percentage composition of biogas was analyzed for determining the operative of the system. Results The production of biogas showed of 52.55% mol of methane concentration which it fed one blowtorch and one kitchenette. The bio-digester effluents showed appreciable amounts of nitrogen, potassium, phosphates, calcium, magnesium and sodium but with E. coli presence; the reason why the bio-digester effluent was treated later by a second fermentation inoculated with mountain effective microorganism, post-treatment which eliminated in 100% E. coli presence. Conclusion Both processes showed the viability as treatment of the bovine manure which brings renewable energy and effluents with nutritive loads to use it as a biofertilizer without risks to health and humanity. The project was located at the tropical zone into the Choco forest, at an average altitude of 1110 m above sea level and an average temperature annual of 21â22 °C.